Tutupan Terumbu Karang pada Kedalaman Berbeda di Perairan Pantai Batu Sungu, Desa Les, Kabupaten Buleleng - I Putu Dede Charles Dharma Saputra; IGB Sila Dharma; Yulianto Suteja; Widiastuti Widiastuti (Journal of Marine Research and Technology, 2021)
Bali island has many magnificent underwater coral reef gardens that attract tourists. Besides Pemuteran and Menjangan island waters, Batu Sungu water has also potential to be a new tourist destination. Thus, to determine the potency and management plan in Batu Sungu waters, this research aimed to examine the overall coral cover, coral growth forms, other benthic forms, and each of their components in 5 and 10 m depths. The overall coral cover, coral growth forms, other benthic forms, and each of their components were counted by using the Line Intercept Transect (LIT) method. Before collecting data, study sites were observed by using the Manta Tow method. Data were collected in 2 depths (5 dan 10 m) with 5 sites each (replicates) that separates within 50 to 150 m. A 25 m LIT was spread parallel to the coastline above the reefs. Live coral colonies, other benthic forms below the transects were measured for the number, length, and growth forms. Water quality was measured in situ (temperature, current, and clarity) and ex situ (pH). Results showed that the category of coral coverage in Batu Sungu water is "good” in 5 m and "moderate” in 10 m whereas there was no significant difference among each component of the overall coral cover. The most dominant coral growth form among the 2 depths was Coral Massive whereas significantly abundant in 5 m. Moreover, the number of Coral Foliose was found significantly high in the same depth. Other coral growth forms were relatively similar in numbers in two depths. As likewise, the cover of other benthic forms and its component were not significantly different among two depths, except Dead Coral with Algae which significantly plentiful in 5 m. Sand was dominantly found in two depths with no significant difference. Furthermore, Coraline Alga was only observed in 5 m, however, there were no Macroalga and Alga Assemblages found at this depth. It is assumed that the similarity number of the overall coral cover, coral growth forms, other benthic forms, and each of their components is related to the alikeness of water quality among the two depths.